Karakteristik Gejala dan Tingkat Kejadian Penyakit Kuning Keriting Tanaman Cabai (Capsicum sp) dalam Budidaya Sistem Organik - Dila Febria; Betari Safitri; Nanang Wahyu Prajaka; Yeni Yeni; Raida Kartina; Sekar Utami Putri (Journal of Horticulture Production Technology, 2023)
Organic chili cultivation has become a necessity nowadays as awareness increases about the dangers of chemical residues used in conventional cultivation practices. Chili is one of three main of vegetables commodities in Lampung. However, pepper yellow leaf curl disease is still a major obstacle faced by farmers to increase chili productivity. Therefore, the aim of this research is to study the characteristics of symptoms and the incidence rate of pepper yellow leaf cull disease of Capsicum annuum L. and Capsicum frutescens in organic cultivation practice. The results shown that the characteristics or early symptoms of pepper yellow leaf curl disease on chilies are yellowing of young leaves, mosaic and malformation which are found in C. annuum L and C. frutescens. The intensity of disease attacks on chili plants by giving POC from the Mimosa pudica roots (PM) gave positive efect with an average low attack intensity in the 8th week, namely 32% compared to giving POC from bamboo roots (AB) with an average attack intensity 45.5%. This indicates that POC from the roots of Mimosa pudica (PM) is capable of being a bioprotectant for chili plants. The application of POC type 3 also provided a positive response with a low intensity of pepper yellow leaf curl disease on C. frutescens.